New insights in the interactions between African trypanosomes and tsetse flies. - (:unkn) unknown (My University, 2013)
African trypanosomiases are vector-borne diseases of human and their livestock, with devastating socio-economical consequences for the Sub-Saharan African continent. These diseases are caused by flagellated unicellular parasites named African trypanosomes that are almost exclusively transmitted by the bite of tsetse flies. Here, both male and female tsetse flies are obligatory blood feeders able to carry and transmit trypanosomes during their entire life span. Two species of African trypanosomes are responsible for Human African Trypanosomiasis (HAT), also known as sleeping sickness: Trypanosoma brucei gambiense in Central/West Africa and T. b. rhodesiense in East/Southern Africa. The T. b. gambiense transmission cycle is mostly from human to human with an occasional involvement of an animal reservoir. The T. b. rhodesiense transmission cycle mainly involves wild and domestic animals, but intensified human-to-human transmission may occur during epidemics. There are no prophylactic drugs or vaccines available to prevent HAT and the few available treatments present a complex posology and severe side effects (Fevre et al., 2006; Brun et al., 2009). In 2011, less than 10,000 new cases were reported (Simarro et al., 2012), with many more cases probably remaining undetected as sleeping sickness occurs in remote rural areas. It is estimated that approximately 70 million people within tsetse-fly infested areas are at different levels of risk of contracting HAT, especially in countries as the Democratic Republic of Congo, Angola, South-Sudan, and the Central African Republic (Simarro et al., 2012; WHO, 2012). In addition to their importance in public health, at least seven other species of African trypanosomes cause severe disease in livestock known as African Animal Trypanosomiasis (AAT) or nagana. T. vivax and T. con-golense are the major pathogens of cattle and other ruminants, while T. simiae, T. godfreyi, and T. suis causes high mortality in domestic pigs.
Keywords: African Research